The influence of various reef sounds on coral‐fish larvae behaviour. Issue 5 (18th March 2015) - Parmentier, E.; Berten, L.; Rigo, P.; Aubrun, F.; Nedelec, S. L.; Simpson, S. D.; Lecchini, D.
<x xml:space="preserve">Abstract</x> The swimming behaviour of coral‐reef fish larvae from 20 species of 10 different families was tested under natural and artificial sound conditions. Underwater sounds from reef habitats (barrier reef, fringing reef and mangrove) as well as a white noise were broadcasted in a choice chamber experiment. Sixteen of the 20 species tested significantly reacted to at least one of the habitat playback conditions, and a range of responses was observed: fishes were (1) attracted by a single sound but repelled by none (e.g. white‐banded triggerfish Rhinecanthus aculeatus was attracted by the barrier‐reef sound), (2) repelled by one or more sounds but attracted by none (e.g. bridled cardinalfish Pristiapogon fraenatus was repelled by the mangrove and the bay sounds), (3) attracted by all sounds (e.g. striated surgeonfish Ctenochaetus striatus), (4) attracted and repelled by several sounds (e.g. whitetail dascyllus Dascyllus aruanus was attracted by the barrier‐reef sound and repelled by the mangrove sound) and (5) not influenced by any sound (e.g. convict surgeonfish Acanthurus triostegus). Overall, these results highlight two settlement strategies: a direct selection of habitats using sound (45% of the species), or a by‐default selection by avoidance of certain sound habitats (35%). These results also clearly demonstrated the need to analyse the influence of sounds at the species‐specific level since congeneric and confamilial species can express different behaviours when exposed to the same sounds.